2019
DOI: 10.17222/mit.2018.116
|View full text |Cite
|
Sign up to set email alerts
|

A novel method for statistical pattern recognition using the network theory and a new hybrid system of machine learning

Abstract: The increase in wear resistance of cast irons after laser treatment is due not only to the corresponding structural and phase composition, but also to the improvement in the friction conditions due to the graphite retained in the laser impact zone. Also, laser hardening increases the wear resistance of steels and some other alloys in terms of the friction in alkaline and acidic environments. In this article we present a new method for a hybrid system of machine learning using a new method for statistical patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…utilize when structuring data on hyperplanes. Previous studies [1,6] suggested that the RBF function worked better for tribological data. Two variables, the kernel coefficient (γ) and the regularization factor (C), determine how well an SVM model performs.…”
Section: Machine Learning (Ml)mentioning
confidence: 98%
See 1 more Smart Citation
“…utilize when structuring data on hyperplanes. Previous studies [1,6] suggested that the RBF function worked better for tribological data. Two variables, the kernel coefficient (γ) and the regularization factor (C), determine how well an SVM model performs.…”
Section: Machine Learning (Ml)mentioning
confidence: 98%
“…Because of its atomically flat surfaces and ultrathin layers, graphene has applications at both the nano and microscales. Graphene lasts a long time since it has a high mechanical strength [6]. Using the nanoindentation method of atomic force microscopy, Arun et al [7] determined that graphene is the most robust material yet quantified for monolayer graphene membranes.…”
Section: Introductionmentioning
confidence: 99%